AN ANALYSIS OF FLOUTING MAXIM IN “THE LION KING 2019” MOVIE - Mutiah Mutiah; Afriana Afriana (IKIP Siliwangi, 2024)
The purpose of the study is to identify the type of flouting maxims in the character in the movie from the data source from the movie “The Lion King 2019” which utterances flouting the maxim. The flouting maxim used the theory by Grice, (1975) cooperative principle which there are four types of flouting maxim: flouting maxim of quality, flouting maxim of quantity, flouting maxim of manner and the last type flouting maxim of relation. The researcher used the qualitative method by Creswell, (2018) Then collecting the data used is an observation method. The technique used note-taking. In addition, used the theory identify the pragmatics approach used to analyze the data. The method used to analyze the data is the identification method, the techniques analysis used identity method by Merriam and Tissdell, (2016). Results found there are fifteen types of flouting maxims there are five flouting maxims of quality, six flouting maxims of quantity, one flouting of manner, and three flouting of relation. Based on the result and discussion are very important in understanding the flouting maxim and are useful for speakers and hearers in creating cooperative communication.